DETERMINAN DAYA DUKUNG SISTEM INFORMASI PENGADAAN BARANG DAN JASA PADA PEMERINTAH DAERAH KABUPATEN MUNA BARAT - Rahman Tandi; Muhammad Amir; La Ode Muhammad Syawal (Journal Publicuho, 2022)
The purpose of this study is to analyze the determinants of the carrying capacity of information systems in procurement services for goods and services. The approach used in this study is a qualitative approach. The technique used in determining informants in this study is a purposive technique, namely the technique of assigning informants with certain criteria that are in accordance with the research objectives. The informants of this study were determined to be as many as 5 (five) people taken from participants and customers. The data analysis used in this study is an interactive model qualitative data analysis. The results showed that the main determinants of the carrying capacity of information system systems on organizational performance are information technology infrastructure, organizational structure, human resources, and available budgets